If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 57.85 = 1.75 + 3.6 + d Combine like terms: 1.75 + 3.6 = 5.35 57.85 = 5.35 + d Solving 57.85 = 5.35 + d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-1d' to each side of the equation. 57.85 + -1d = 5.35 + d + -1d Combine like terms: d + -1d = 0 57.85 + -1d = 5.35 + 0 57.85 + -1d = 5.35 Add '-57.85' to each side of the equation. 57.85 + -57.85 + -1d = 5.35 + -57.85 Combine like terms: 57.85 + -57.85 = 0.00 0.00 + -1d = 5.35 + -57.85 -1d = 5.35 + -57.85 Combine like terms: 5.35 + -57.85 = -52.5 -1d = -52.5 Divide each side by '-1'. d = 52.5 Simplifying d = 52.5
| 57.85=3.6+1.75xd | | 57.85=1.75+3.6xd | | 2L=46 | | 5L=46 | | 6L=46 | | 4l=46 | | 66.55=1.8+1.75*d | | 66.55=1.75+1.8+d | | 13/x=30/42 | | d=66.55-1.75-1.8 | | F(x)=x^3+3x^2 | | 20=6(y-6)+2y | | 50=r+8 | | 50=r+r-8 | | 50-8=r | | 50-8=2r | | X/23=15/33 | | x-11=17-3x | | X/22 | | -7y-21=0 | | c=18+3c | | 5d=40-5d | | 7d-8=-d+56 | | 4j-3=-2j+45 | | 5y+6=-y+66 | | 36c-27=3(8c+3) | | 2(4c-5)=2c+8 | | 8y=15+3y | | -3=3(u+7)-6u | | 6a-8=a+32 | | 9j-9=3j+39 | | 9j+9=3j+39 |